Development of high protein groundnut (Arachis hypogaea L.) mutant through induced mutagenesis: DEVELOPMENT OF HIGH PROTEIN GROUNDNUT MUTANT THROUGH INDUCED MUTAGENESIS - SUVENDU MONDAL; ANAND M BADIGANNAVAR (Journal of Oilseeds Research, 2016)
Groundnut is used as a food crop for its oil, protein content and other valuable bioactive compounds. Induced mutagenesis played an important role to generate genetic variability in this crop. Here we report the identification of a high protein mutant from a mutagenized population of a rust resistant breeding line, TG 66. The mutant, TGM 206 revealed a 19.8 per cent increment of seed protein content compared to its parent. Through protein analysis it was found that the conarachin fraction was selectively increased in this mutant.